The effectiveness of the event in contemporary Iraqi formation - Fadhil Abdul Hakeem Abdul Rid (الاكاديمي)
The research problem entitled (The effectiveness of the event in contemporary Iraqi painting) dealt with a study in the concept of the event. The study included four chapters. The first chapter was devoted to the theoretical framework represented by posing (the research problem), which raised the following question: What is the role of the effectiveness of the event that appeared in the arena? Iraq on the contemporary Iraqi plastic work. Did these events constitute an intellectual and aesthetic change in the contemporary Iraqi work?